PENGARUH GREEN INNOVATION TERDAHAP ECONOMIC PERFORMANCE DENGAN ENVIRONMENTAL MANAGEMENT ACCOUNTING SEBAGAI VARIABEL MODERASI - Mariyamah Mariyamah; Susi Handayani (JURNAL AKUNTANSI DAN AUDITING, 2019)
This study aims to examine empirically the effect of green innovation on economic performance and environmental management accounting as a moderate variable. This research method uses quantitative research methods. The sample of this study was manufacturing companies listed on the Indonesia Stock Exchange and participated PROPER program in the period 2016-2018. Based on the sampling technique, there were 155 companies. The data analysis technique uses Moderated Regression Analysis with the application of SPSS 25. The independent variable in this study is green innovation, which is green product innovation and green process innovation. The dependent variable in this study is economic performance measured by ROA. The moderating variable in this study is environmental management accounting measured by the eco-efficiency ratio. The results of this study show that green innovation has a positive effect on economic performance and environmental management accounting cannot moderate the relationship between green innovation and economic performance